Computer-Aided Design of Stub-Girder System - Wang, P.C.; Gotschall, John A. (Engineering Journal, 1980)
The stub-girder system for high-rise buildings is a relatively new and innovative concept in structural floor framing. The system, developed by Dr. Joseph Colaco in 1972, has gained considerable attention in recent years as a viable alternative to the traditional method of structural floor framing. The stub-girder system, in an effort to minimize overall space requirements while maintaining an independence between the various building systems, combines space for the mechanical ductwork in the design of the structural system. The result is an increase in the efficiency of both the structural frame and the mechanical layout, combined with a reduction in both space and material required. To date, several major buildings have been designed using the stub-girder system. Yet, the stub-girder system has been unable to gain wide-spread application in the construction industry due to the inability of average design firms to carry out the necessary computer analyses.